DAMPAK PUASA TERHADAP KESEHATAN MENTAL PERSPEKTIF AL-QUR’AN DAN HADITS - Lilis, Lilis (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2024)
This scientific article discusses the impact of fasting on mental health, so this research aims to analyze the benefits of fasting for a person's mental health. The main focus of the research is to explore the benefits of fasting in improving mental health, including its ability to provide calm, control anger and overcome negative things. This research uses literature and library research methods to explore various sources that support the author's argument by analyzing various articles that discuss the importance of fasting for a person's mental health. From the research results, it can be seen that fasting is not only limited to religious obligations but has great benefits, including for mental health, such as providing calm and increasing self-control. Fasting not only contributes to physical health, but also improves mental health by reducing symptoms of anxiety and depression. The implications of these findings are important for fasting individuals and mental health professionals, and provide insight for the development of more comprehensive health strategies. Understanding the relationship between fasting and mental health can support emotional well-being in an increasingly complex society.